Validação do nível de expressão gênica diferencial dos genes actina, tripsina e phosrrestin ii entre larvas e adultos de anopheles darlingi root, 1926 (diptera: culicidae) - Souza, Ketlen Christine Nunes de (2011)
The Anopheles (Nyssorhynchus) darlingi Root, 1926 is considered the primary vector of malaria and the species has the sharpest endophagous and anthropophily between the South American anopheline, with the biggest records in the Amazon region. Malaria is a parasitic disease that affects more than 90 countries worldwide, where about 40% of the population live in areas at risk because they are difficult to control. In recent years, studies of alternative detection and quantification of expression gene have been carried out, as the amplification and analysis of cDNA fragments by the method of Polymerase Chain Reaction in Real Time (qRTPCR), one of the technologies employed in post-genomic age. In this sense, validated the level of genes expression sampled in silico, in advance, between two stages of development of An.darlingi (larvae and adults). An. darlingi samples were obtained in the neighborhood Puraquequara (03º 03' 06.95'' S and 59º 52' 31.38'' W), of Manaus City, Amazonas State, identified and treated individually for oviposition. Larvae of the 1st or 2nd instar were used for total RNA extraction with the Extraction and Purification Quiagen® Kit. We obtained the complementary strand of mRNA (cDNA) with the kit from Promega® . The qRT-PCR method was according to the system SYBR® Green (Applied Biosystems® ) with reactions performed in the ABI-7500 thermocycler™ Real-Time PCR System, Applied Biosystems® . Was analyzed for gene expression, four genes of interest: Actin, Trypsin, Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and Phosrestin II (Arrestin-A). Among these, GAPDH showed little variation in their level of gene expression in larvae and adults. Therefore, this gene was chosen as reference. Larvae (L1L2) were chosen as normalizing the amplification reactions. In relative quantification, the actin expression was higher in adult compared with larvae, validating the results normalized level of expression in silico library of ESTs from An. darlingi. Trypsin was mainly expressed in larvae. In A. darling the Phosrestin II - (Arrestin-A) expression was higher in larvae than in adults. These data validate the differential gene expression between L1L2 and adults of An. darlingi, useful for understanding the biology and evolution gene of this important malaria vector in South America.